Sustainable usage of demolished concrete waste as a sub-base material in road pavement - Mazhar, Mohd. Aamir; Alam, Pervez; Ahmed, Sirajuddin; Khan, Mohammed Sharib; Adam, Farhan Ali (Frontiers in Sustainability, 2023)
Recycled concrete aggregate, waste rock, crushed stone aggregate, reclaimed asphalt pavement, crushed clay brick, fine recycled glass, and gravel are some of the things that are left behind when concrete buildings are torn down. These things are a big problem for many countries around the world. More and more people want to find smart ways to use the waste that these substances make. To protect the environment and natural resources and to keep damage to the environment to a minimum, it is important to deal with this issue locally. Several studies have shown that old concrete is strong and can be used as a green material. This will make construction cheaper in the long run. Thus, the goal of this research was to find out how well demolished concrete waste works and what its engineering properties are so that it could be used in the base and sub-base of road pavements. The old concrete waste aggregates were used to replace the new or fresh aggregates in a range from 0% to 100% by weight. When demolished concrete waste aggregates were used instead of new aggregates, the water absorption went up from 1.58 to 4.65%. This shows that the water-cement ratio got better. The crushing value went up from 26.54 to 55.29%, the impact value went up from 27.86 to 58.05%, and the abrasion value went up from 26.96 to 35.58%. Based on the results of this study, the sub-base of roads can be made from a mix of 50% recycled aggregates and 50% new aggregates. Reusing concrete waste from buildings that have been torn down as a sub-base material will help reach social, economic, and environmental sustainability.